Pengaruh Persepsi Konsumen terhadap Keputusan Pembelian Bibit Ayam Murung Panggang di Desa Murung Panggang - Novia Sari; Azwar Saihani; Rum Van Royensyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2018)
This study aims to identify consumer perceptions of roasted broiled chicken seeds and determine the effect of consumer perceptions in making decisions to purchase roasted mulberry chicken seeds in Murung Panggang Village, South Amuntai District. Based on the sum of the Likert scale values ​​that the average score of the overall perception statement is 100.9, which is in the area agreed. Based on the results of the coefficient of determination analysis (R2) of the regression equation as a whole there are influences of independent variables including price variables, quality variables, and producer service variables on purchasing decisions that can be seen in the adjusted R Square value of 0.644. From the results of the t-test, the price factor does not significantly influence the purchasing decision with a significant value of 0.782> 0.05, so H0 is rejected, and H1 is accepted. Quality factors have no significant effect on purchasing decisions with a significant value of 0.053> 0.05 so that H0 is accepted and H1 is rejected, and factor levels of producer service have a significant effect on purchasing decisions with a significant value of 0,000 <0.05, so H0 is rejected and H1 is accepted.